2022
DOI: 10.1101/2022.09.11.507473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Percolate: an exponential family JIVE model to design DNA-based predictors of drug response

Abstract: Motivation: Anti-cancer drugs may elicit resistance or sensitivity through mechanisms which involve several genomic layers. Nevertheless, we have demonstrated that gene expression contains most of the predictive capacity compared to the remaining omic data types. Unfortunately, this comes at a price: gene expression biomarkers are often hard to interpret and show poor robustness. Results: To capture the best of both worlds, i.e. the accuracy of gene expression and the robustness of other genomic levels, such a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…On the other hand, these methods underperformed with respect to baseline non-linear methods in terms of generation coherence. Regarding downstream supervised tasks, we observed that joint embedding can lead to improved performance when only a single modality is available in the test data, which verifies previous results for linear methods [27]. If data from both modalities are available at test time, joint embedding did not provide a significant advantage in the tasks that we tested here.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, these methods underperformed with respect to baseline non-linear methods in terms of generation coherence. Regarding downstream supervised tasks, we observed that joint embedding can lead to improved performance when only a single modality is available in the test data, which verifies previous results for linear methods [27]. If data from both modalities are available at test time, joint embedding did not provide a significant advantage in the tasks that we tested here.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, these methods underperformed with respect to baseline non-linear methods in terms of generation coherence. Regarding downstream supervized tasks, we observed that joint embedding can lead to improved performance when only a single modality is available in the test data, which verifies previous results for linear methods [ 29 ]. If data from both modalities are available at test time, joint embedding did not provide a significant advantage in the tasks that we tested here.…”
Section: Discussionsupporting
confidence: 86%
“…sincei accommodates these popular choices through the log1p-PCA, LSA, and LDA methods. Furthermore, we also offer a scalable implementation of GLM-PCA 12,13 , a flexible dimensionality reduction method that can accommodate a broad range of signal types, such as counts (Poisson), binary (Bernoulli), ratio (Beta). Developers can easily extend this list, providing users with the flexibility needed to explore diverse statistical modeling options, particularly instrumental in developing novel assays.…”
Section: Dimensionality Reduction and Clustering Of Cells Based On Ge...mentioning
confidence: 99%